2014
DOI: 10.3923/pjbs.2014.574.577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxidative Stress Status Through MN Test and Serum MDA Levels in PCOS Women

Abstract: Polycystic Ovary Syndrome (PCOS) is a multifactorial reproductive healthcare problem affecting 4-12% of women and a leading cause of female infertility worldwide. The potential genetic contributors of PCOS are unclear. However, over the past decade emerging evidence has shown that increased Oxidative Stress (OS) and decreased antioxidant status were often linked with PCOS. The present case-control study was aimed to assess the reactive oxygen species induced OS in women from South India. A total of 164 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Micronucleus (MN) frequency, evaluated by cytokinesis block micronucleus index, which reflects genomic instability, is increased in PCOS patients compared with controls [ 158 – 161 ]. Furthermore, women with PCOS show a significant increase in DNA strand breakage and H 2 O 2 -induced DNA damage [ 162 ].…”
Section: Polycystic Ovary Syndrome and Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronucleus (MN) frequency, evaluated by cytokinesis block micronucleus index, which reflects genomic instability, is increased in PCOS patients compared with controls [ 158 – 161 ]. Furthermore, women with PCOS show a significant increase in DNA strand breakage and H 2 O 2 -induced DNA damage [ 162 ].…”
Section: Polycystic Ovary Syndrome and Cancersmentioning
confidence: 99%
“…Serum MDA levels, an OS marker, were observed to be positively correlated with MN in PCOS patients but not the normal [ 158 ]. In addition, mtDNA copy number was negatively correlated with indices of insulin resistance, waist circumference, and triglyceride levels and positively correlated with sex hormone-binding globulin levels [ 163 ].…”
Section: Polycystic Ovary Syndrome and Cancersmentioning
confidence: 99%
“…Zuo et al ( 17 ) reported that variable oxidative stress in PCOS, instability of genes, and DNA mutations increased the risk and potentially contributed to the pathogenesis of gynecologic cancers. Deepika et al ( 18 ) reported that serum malondialdehyde levels of oxidative stress markers showed a positive correlation with MN in patients with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies about the increased oxidative stress markers in patients with PCOS and this mechanism has been accepted to be related to mutagenesis in these patients ( 5 , 15 ) . Some investigators reported a positive correlation between oxidative stress and lipid peroxidation and genotoxicity ( 16 , 17 , 18 ) . This type of damage can lead to chromosomal losses and rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation